Quality and Accountability in Healthcare Delivery : Audit Evidence from Primary Care Providers in India - Das, Jishnu (World Bank, Washington, DC, 2015)
This paper presents direct evidence on the quality of health care in low-income settings using a unique and original set of audit studies, where standardized patients were presented to a nearly representative sample of rural public and private primary care providers in the Indian state of Madhya Pradesh. Three main findings are reported. First, private providers are mostly unqualified, but they spent more time with patients and completed more items on a checklist of essential history and examination items than public providers, while being no different in their diagnostic and treatment accuracy. Second, the private practices of qualified public sector doctors were identified and the same doctors exerted higher effort and were more likely to provide correct treatment in their private practices. Third, there is a strong positive correlation between provider effort and prices charged in the private sector, whereas there is no correlation between effort and wages in the public sector. The results suggest that market-based accountability in the unregulated private sector may be providing better incentives for provider effort than administrative accountability in the public sector in this setting. While the overall quality of care is low both sectors, the differences in provider effort may partly explain the dominant market share of fee-charging private providers even in the presence of a system of free public healthcare.